Qisshotul Qur’an: Upaya Penguatan Literasi Keagamaan Bagi Siswa SD Al-Qur’an Ummul Quro Pamekasan - Rois Imron Rosi; Ach Syafiq Fahmi (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2022)
Literacy has become a problem in the context of Indonesia. Data showed that 71% of 34 provinces are categorized as having a low literacy index. Currently, another kind of literacy appears and seen as a very important kind of literacy to face the challenges of the 21st century called religious literacy. Religious literacy seen as a kind of literacy that aims to develop religious insight. Some researches argued that this kind of literacy is rarely noticed by academicians especially at the elementary school level. So, this research is an attempt to describe one of the efforts of teacher in elementary school in order to strengthen this religious literacy through Qisshotul Qur’an Subject as local content subject. Using the case study technique of qualitative research, this study showed that this subject is trying to strengthen student’s religious knowledge by providing Qur’anic stories based on 25 prophets written in the Qur’an. The material is presented in the form of story to make student interested. While student interest to the material, their understanding also will increase. One of the student’s interest shown by their enthusiasm. This kind of subject proven to be able to strengthen student’s religious literacy through their development on understanding of exemplary stories of the prophets as well as the exemplary application in student’s daily life. Every teacher has ensured the lesson content internalization through exemplary control inside and outside the classroom.